(untitled) (Journal of Engineering, 2011)
In this work an experimental study is performed to evaluate the thermal performance of locally made closed loop solar hot water system using a shell and helical coiled tube heat exchanger as a storage tank. Several measurements are taken include inlet and outlet temperatures of both collectors and supply water and temperature distribution within the storage tank. This is beside the water flow rate in both collectors and load cycle. The main parameters of the system are obtained.